Efficacy and safety of over-the-scope clips for gastrointestinal bleeding: a systematic review and meta-analysis - Chandrasekar, Viveksandeep Thoguluva; Desai, Madhav; Aziz, Muhammad; Patel, Harsh K.; Gorrepati, Venkata Subhash; Jegadeesan, Ramprasad; Rai, Tarun; Sathyamurthy, Anjana; Murino, Alberto; Hassan, Cesare; Repici, Alessandro; Sharma, Prateek (Endoscopy, 2019)
Background The over-the-scope clip (OTSC) has been increasingly utilized for the management of gastrointestinal (GI) bleeding. Limited efficacy data are currently available from large-scale studies.Methods An electronic database search was conducted for eligible articles using OTSCs for hemostasis in GI bleeding. The primary outcome was the rate of definitive hemostasis after primary hemostasis and without rebleeding at follow-up. Secondary outcomes were: primary technical success, primary clinical success, rebleeding, and failure rates. Pooled rates were expressed as proportions of patients with events over total patients, 95 % confidence limits (CI) with heterogeneity, and P values of < 0.05 for significance.Results A total of 21 studies (n = 851) were analyzed (62.2 % males), with a median patient age of 69.7 years. The definitive hemostasis rate was 87.8 % (95 %CI 83.7 % – 92 %) after a median follow-up of 56 days. The OTSC was successfully deployed in 97.8 % of patients (95 %CI 96.7 % – 98.9 %) and the primary clinical success rate was 96.6 % (95 %CI 95.1 % – 98.2 %). Rebleeding was seen in 10.3 % of patients (95 %CI 6.5 % – 14.1 %). The failure rate of OTSCs was 9 % (95 %CI 5.2 % – 12.8 %) when used as first-line treatment and 26 % (95 %CI 16.1 % – 36.0 %) when used as second-line treatment.Conclusion This systematic review showed high rates of definitive hemostasis, technical success, and clinical success, along with low rebleeding rates when OTSCs were used for the treatment of GI bleeding. The lack of randomized controlled trials of OTSC vs. other therapies makes comparison with conventional treatment difficult.